Eruptive Nevi Mimicking Wart-Like Lesions under Selective BRAF Inhibition in a 37-Year-Old Female Melanoma Patient - Laurenz Schmitt; Tamara Schumann; Oliver Inhoff; Christoph Löser; Martin Rebel; Edgar Dippel (Karger Publishers, 2013)
Background: The BRAF inhibitor vemurafenib is state of the art in therapy of patients with malignant melanoma in non-resectable stage III or stage IV and evidence of oncogenetic BRAF mutation. Multiple cutaneous side effects like rash and keratoacanthoma-like lesions have been described so far. Case Report: We report a patient who presented multiple wart-like lesions under therapy with vemurafenib. Histologically we have seen multiple melanocytic nevi with a wart-like appearance. One melanoma in situ developed on the left forearm. Conclusions: Eruptive nevi and induction of melanoma may be a further side effect in patients undergoing a therapy with BRAF inhibitors.